1997
DOI: 10.1177/014107689709001206
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Current Practice and a near Patient Testing Method for Oral-Anticoagulant Control in General Practice

Abstract: When oral anticoagulant control is monitored in general practice, venous blood samples are usually transported to a central laboratory for determination of international normalized ratio (INR). An alternative is near patient testing by a commercial method. In a rural general practice 27 km from a central haematology laboratory, whole blood samples were drawn from patients receiving oral anticoagulants and analysed by three methods: after centrifugation, plasma separated and frozen in liquid nitrogen, transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…There have been few RCTs in this area and none have investigated all the areas covered in this Trial or at the scale of this Trial either in terms of the number of practices, the number of patients or the number of pathology tests included. 8,18,33,34,[58][59][60] No past trials and very few observational studies 16,17 have investigated the influence of geographic location on PoCT. The results of the PoCT Trial should provide a sound evidence base as to whether PoCT (for the three conditions) should be implemented by the government in Australian general practice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been few RCTs in this area and none have investigated all the areas covered in this Trial or at the scale of this Trial either in terms of the number of practices, the number of patients or the number of pathology tests included. 8,18,33,34,[58][59][60] No past trials and very few observational studies 16,17 have investigated the influence of geographic location on PoCT. The results of the PoCT Trial should provide a sound evidence base as to whether PoCT (for the three conditions) should be implemented by the government in Australian general practice.…”
Section: Resultsmentioning
confidence: 99%
“…44 Four of the RCTs investigated PoCT with another intervention. 8,18,21,34,58,59 The geographical setting included the United Kingdom (n=13) 8,16,18,21,33,[60][61][62][63][64][65][66][67] , Australia (n=7) 17,23,47,[68][69][70][71] , USA (n=5) 44,58,[72][73][74] , Belgium (n=2) 34,59 , Sweden (n=1) 75 and Ireland (n=1). 76 A description of the 29 studies included in the review is reported in Table 13 and Table 14.…”
Section: Excluded Studiesmentioning
confidence: 99%
See 3 more Smart Citations